Bulletin of FVR "Sermons" volume IV : on board the Philippine ship (Filipinos together) - Ramos, Fidel V. ([Manila, Philippines] : Ramos Peace and Development Foundation and the Manila Bulletin, 2009)
This fourth volume of FVR's selected Sunday columns in the Manila Bulleting covers a 12-month period from July 2008 to June 2009. This volume is being released as RPDEV's special 10th anniversary edition.
Chapter I : Modernizing our Philippine ship -- Chapter II : Promoting national unity -- Chapter III : Exploiting opportunities -- Chapter IV : Leadership and heroism
Includes index.
Keywords: RAMOS, FIDEL V -- 1928-